2016
DOI: 10.1039/c6tb01355d
|View full text |Cite
|
Sign up to set email alerts
|

Robust glucose oxidase with a Fe3O4@C-silica nanohybrid structure

Abstract: Biomolecules, especially enzymes, usually have poor thermal and operational stability as well as limited reuse cycles, which greatly limit their industrial practices. Inspired by the biomineralization strategy evolved by natural organisms, we suggest nanohybrid enzyme formulation by in situ encapsulating enzyme loaded functional Fe 3 O 4 @C nanoparticles with silica. By using glucose oxidase (GOD) as an example, we demonstrate that the obtained enzyme-material hybrids are featured by their significantly enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
5
24
0
Order By: Relevance
“…The selection of suitable ureolytic bacteria is highly important in urease-based MICP technique. The enzymes of the bacteria are thermal sensitive and can readily be denatured by even a slight change of environmental temperature [22]. Most of the MICP studies have employed Sporosarcina pasteurrii for urea hydrolysis due to the highly active urease enzyme [5,6,11,13,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The selection of suitable ureolytic bacteria is highly important in urease-based MICP technique. The enzymes of the bacteria are thermal sensitive and can readily be denatured by even a slight change of environmental temperature [22]. Most of the MICP studies have employed Sporosarcina pasteurrii for urea hydrolysis due to the highly active urease enzyme [5,6,11,13,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Storage stability is an important advantage of immobilized enzymes over their free counterparts since some previous investigations have already reported that free biocatalysts can usually lose their activities fairly quickly during storage [52,53,54,55]. In our case, the storage stability of free and immobilized His 6 - Ec PepQ was compared and the relevant research results are shown in Figure 6A.…”
Section: Resultsmentioning
confidence: 88%
“…Based on the established FTIR spectra of iron oxides [51], the low-intensity band at approximately 3460 cm −1 can be assigned to OH stretching due to the presence of water traces. Interestingly, the 3460 cm −1 signal can also be seen in the FTIR spectra of iron oxides synthesized by different research teams [8,9,40,42,52,53]. However, the exact reason for the presence of water traces in the prepared iron oxides remains unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The EDS test of N 5 D 1 W 17 hydrogel further confirmed that W element was present in the hydrogel [ Figure 2 groups, such as ammonium groups and ester groups. 38 The maximum degradation temperature (T max ) for the hydrogel sample was found at 344.8 8C with a weight loss of 47.86 wt % at third degradation stage, which could be attributed to the weight loss of functional groups and the polymer main-chain scission and the destruction of crosslinked network structure. In the fourth stage, the further decomposition of the organic matter in the hydrogel taken place in 454-540 8C.…”
Section: Synthesis Of P(nipam-co-dmc)/na 2 Wo 4 Hydrogelmentioning
confidence: 91%